Effects of Nanosilica on Early Age Stages of Cement Hydration. (12th October 2017) - Torabian Isfahani, Forood; Redaelli, Elena; Li, Weiwen; Sun, Yaru
Abstract : Effects of nanosilica on cement hydration have been broadly investigated in the literature and early age cement hydration, as a whole, has been mainly considered, disregarding the substages of the hydration. The hydration of cement is characterized by different substages and nanosilica effect on the hydration could be a result of diverse, even contradictory, behavior of nanosilica in individual stages of the hydration. In this study, effects of nanosilica on different substages of cement hydration are investigated. Isothermal calorimetry results show that at early ages (initial 72 hours) the effects of nanosilica depend on the phenomenon by which the hydration is governed: when the hydration is chemically controlled, that is, during initial reaction, dormant period, and acceleratory period, the hydration rate is accelerated by adding nanosilica; when the hydration is governed by diffusion process, that is, during postacceleratory period, the hydration rate is decelerated by adding nanosilica. The Thermal Gravimetric Analysis on the samples at the hardened state (after 28 days of curing) reveals that, after adding nanosilica, the hydration degree slightly increased compared to the plain paste.